PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VISUAL TERHADAP KEMAMPUAN KOGNITIF SISWA KELAS IV SDN 005 LANGGINI - Yolanda Aprila Koto; Muhammad Syahrul Rizal; Zulfah Zulfah (Universitas Negeri Surabaya, 2021)
This research is motivated by the low cognitive ability of students in grade IV SDN 005 Langgini Bangkinang District, Kampar Regency. One solution to overcome this problem is to use the Problem Based Learning model. The purpose of this study is to see whether or not there is an influence in using the Problem Based Learning model in the learning process for fourth grade students at SDN 005 Langgini. The research method used is Quasi Experiment which is carried out using two classes, namely the experimental class and the control class. Each class will be held three times, in the experimental class learning is carried out using the Problem Based Learning learning model while in the control class using the conventional learning model. The subjects of this study were students of class IVA who became an experimental class of 20 students consisting of 9 male students and 11 female students and class IV B which is the control class as many as 20 students consisting of 8 male students and 12 female students. The results of the students' cognitive abilities were seen from the data obtained during the pretest and posttest. The results of this study showed that in the experimental class the average pretest results of students before applying the Problem Based Learning learning model was 41.5 and the average posttest results of students after using the Problem Based Learning learning model rose to 71.25 so that the average difference from the results the students' pretest and posttest were 29.75%. while in the control class using the conventional model, the pretest score was 42.5 and the posttest score was 55.4, so the difference between the pretest and posttest results was 12.9%. Thus it can be concluded that the Problem Based Learning learning model assisted by visual media has an effect on the cognitive abilities of students in grade IV SDN 005 Langgini